Catalytic fast co-pyrolysis of waste greenhouse plastic films and rice husk using hierarchical micro-mesoporous composite molecular sieve. (1st February 2020) - Li, Zhaoying; Zhong, Zhaoping; Zhang, Bo; Wang, Wei; Seufitelli, Gabriel V.S.; Resende, Fernando L.P.
Graphical abstract: Highlights: Catalytic fast co-pyrolysis of RH and WGPFs over hierarchical catalyst via Py-GC/MS. We designed a hierarchical HZSM-5/MCM-41 catalyst for catalytic fast pyrolysis. Co-pyrolysis of RH and WGPFs leads to a total hydrocarbon yield of 71.1 wt%. Optimum temperature and ratio of RH to WGPFs are 600 °C and 1/1.5, respectively. Abstract: Catalytic fast co-pyrolysis of waste greenhouse plastic films and rice husk over a hierarchical HZSM-5/MCM-41 catalyst was performed in an analytical Py-GC/MS. We evaluated the effect of pyrolysis temperature and the ratio of rice husk to waste greenhouse plastic films on the total peak area of condensable organic products and CO2 . In order to evaluate synergy possibilities among the two feedstocks, we performed non-catalytic pyrolysis and catalytic fast pyrolysis of rice husk and waste greenhouse plastic films separately. In addition, we report results for the catalytic fast co-pyrolysis of the mixture rice husk and waste greenhouse plastic films. The maximum relative content of hydrocarbons from catalytic fast co-pyrolysis of rice husk and waste greenhouse plastic films is obtained at 600 °C. When the mass ratio of rice husk to waste greenhouse plastic films is 1:1.5, the relative content of hydrocarbons reaches a maximum (71.1%). The hierarchical micro-mesoporous composite molecular sieve used in this work has outstanding catalytic activity and increases the relative content of hydrocarbons.